2023
DOI: 10.1007/s00299-023-03052-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the salt tolerance of Nitraria sibirica Pall. based on Pacbio full-length transcriptome sequencing

Panpan Zhang,
Fengxiang Zhang,
Zhiheng Wu
et al.

Abstract: N. sibirica, as a typical halophyte, can not only effectively repair saline-alkali land, but also has high economic value. However, the analysis on its salt tolerance at combining the molecular and physiological levels was little studied. Hence, in this study, the salt tolerance of N. sibirica was analyzed based on Pacbio full-length transcriptome sequencing, and the salt tolerance in the physiological levels was veri ed by key genes. The results found that 89,017 full-length transcripts were obtained, of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…sibirica is a dicotyledonous shrub that belongs to Nitraria L. which is widely used in landscape beautification and ecological restoration of saline-alkali land. It is a typical halophytic plant that can survive extreme drought and saline environments, with great salt tolerance and environmental adaptability making it a nice model for studying the role of 14-3-3 proteins in stress tolerance [23][24][25]. Accordingly, in this study, we identified nine members of the Ns14-3-3 gene family from the genomic data of N. sibirica.…”
mentioning
confidence: 99%
“…sibirica is a dicotyledonous shrub that belongs to Nitraria L. which is widely used in landscape beautification and ecological restoration of saline-alkali land. It is a typical halophytic plant that can survive extreme drought and saline environments, with great salt tolerance and environmental adaptability making it a nice model for studying the role of 14-3-3 proteins in stress tolerance [23][24][25]. Accordingly, in this study, we identified nine members of the Ns14-3-3 gene family from the genomic data of N. sibirica.…”
mentioning
confidence: 99%